Ethics and Religion as Standards for Politics and Leadership in 2024 Indonesian Election (State Islamic Institute of Kudus (IAIN Kudus), 2025)
The Indonesian public, and even the world, were shocked by numerous serious ethical violations during the 2024 general elections, threatening Indonesia’s democracy. Although constitutionally and in existing laws and regulations, there is no legitimate or convincing error in the decisions taken by the leaders of this republic, they have deliberately created ethical problems in the life of the nation and state. Some cases that can be taken generally in Indonesia during the 2024 general elections are Constitutional Court Decision Number 90/PUU-XXI/2023 and the partisanship of state leaders in the presidential and vice-presidential elections. Both issues have shaken the Indonesian people and the international community. Indonesia’s democratic values are being questioned due to the country’s lack of ethical and moral awareness. This article discusses how ethical and moral awareness must be prioritized and mainstreamed in the standards of politics and leadership in Indonesia. This article is a literature study employing a descriptive-analytical method, drawing on reliable sources such as journal articles, newspapers, news, legal decisions, books, and other relevant reading materials. This research offers key insights into the ethical and moral challenges of the 2024 general elections. It concludes that ethical, moral, and religious standards must be prioritized and mainstreamed in Indonesia’s political attitudes and leadership. It also provides guidance to all leaders and prospective leaders on upholding ethical, moral, and religious standards aligned with Indonesia’s democratic culture.